Carriers of the PCSK9 R46L Variant Are Characterized by an Antiatherogenic Lipoprotein Profile Assessed by Nuclear Magnetic Resonance Spectroscopy—Brief Report. Issue 1 (January 2017) - Verbeek, Rutger; Boyer, Marjorie; Boekholdt, S. Matthijs; Hovingh, G. Kees; Kastelein, John J.P.; Wareham, Nicholas; Khaw, Kay-Tee; Arsenault, Benoit J.
Abstract : Objective—: Carriers of the PCSK9 (proprotein convertase subtilisin/kexin 9) R46L genetic variant (rs11591147) are characterized by low levels of low-density lipoprotein cholesterol and a decreased risk of cardiovascular disease. We studied the impact of the R46L variant on lipoprotein size and composition. Approach and Results—: Lipoprotein size and composition were measured by nuclear magnetic resonance spectroscopy in 2373 participants of the EPIC (European Prospective Investigation into Cancer and Nutrition)-Norfolk study. After adjusting for age, sex, and cardiovascular disease status, carriers of the R46L variant (n=77) were characterized by lower concentrations of very low–density lipoprotein particles (85.8±26.2 versus 99.0±33.3 nmol/L; P <0.001), low-density lipoprotein particles (1479.7±396.8 versus 1662.9±458.3 nmol/L; P <0.001), and lipoprotein(a) (11.1 [7.2–28.6] versus 12.4 [6.7–29.1] mg/dL; P <0.001) compared with noncarriers. Total high-density lipoprotein particle and very low–density lipoprotein, low-density lipoprotein, and high-density lipoprotein particle sizes were comparable in carriers and noncarriers. Carriers were characterized by lower secretory phospholipase A2 (4.2±0.9 versus 4.6±1.3 nmol/mL/min; P =0.004) and lipoprotein-associated phospholipase A2 activity (47.5±14.1 versus 52.4±16.2 nmol/mL/min; P =0.02) compared with noncarriers. Conclusions—: Results of this study suggest that carriers of the PCSK9 R46L genetic variant have lower very low–density lipoprotein and low-density lipoprotein particle concentrations, lower lipoprotein(a) levels, and lower secretory phospholipase A2 and lipoprotein-associated phospholipase A2 activity compared with noncarriers. Abstract : Supplemental Digital Content is available in the text.